Influence of crowding on body mass, serum total protein and aminotransferase (ALT, AST) concentration and activity in the feral pigeon "Columba livia f. urbana" - Kasprzak, Mariusz; Ciepliński, Mateusz; Steliga, Aleksandra; Hetmański, Tomasz; Kamiński, Piotr; Grandtke, Monika; Łopińska, Andżelina (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
19 males and 24 females of feral pigeons "Columba livia f. urbana" were transferred from a room with 1.4 individuals/m3 to one with 3.1 individuals/m3. They were fed "ad libitum" during the entire experiment. Body mass, blood serum total protein and transaminase (ALT, AST) concentrations were measured. After a 40-day period of crowding, a statistically significant decrease in serum total protein was observed for both sexes.
Keywords: pigeon; Columba livia f. urbana; body weight; total protein; AST; ALT; crowding